Poly(3, 4-ethylenedioxythiophene) doped with various carbon-based materials as counter electrodes for dye sensitized solar cells. (15th December 2017) - Mustafa, Muhammad Norhaffis; Shafie, Suhaidi; Zainal, Zulkarnain; Sulaiman, Yusran
Abstract: Various carbon-based materials, poly(3, 4-ethylenedioxythiophene) (PEDOT) and titanium dioxide (TiO2 ) were used to fabricate new counter electrodes namely poly(3, 4-ethylenedioxythiophene)-reduced graphene oxide/titanium dioxide (PEDOT-rGO/TiO2 ), poly(3, 4-ethylenedioxythiophene)-nanocrystalline cellulose/titanium dioxide (PEDOT-NCC/TiO2 ) and poly(3, 4-ethylenedioxythiophene)-multiwalled carbon nanotubes/titanium dioxide (PEDOT-MWCNT/TiO2 ). MWCNT and rGO provided high electrical conductivity and a large surface area, whereas NCC offered a large surface area and high optical transparency which is an important criterion to fabricate a good counter electrode for enhanced dye-sensitized solar cell (DSSC) performance. In addition, carbon-based materials have high availability and low cost compared to platinum-based materials which are more expensive and difficult to source. The PEDOT-NCC/TiO2 counter electrode exhibited good electrocatalytic activity towards tri-iodide ion reduction and yielded a power conversion efficiency of 2.10%, which was much higher compared to PEDOT-rGO/TiO2 (1.11%) and PEDOT-MWCNT/TiO2 (1.29%). PEDOT-NCC/TiO2 also displayed lower charge transfer resistance ( R ct1  = 10.4 Ω·cm 2 ) and higher cathodic peak current density ( I cp  = − 2.60 mA·cm − 2 ) as compared to the other counter electrodes. Graphical abstract: PEDOT-(rGO/MWCNT/NCC)-TiO2 counter electrode. Highlights: PEDOT-rGO/TiO2, PEDOT-NCC/TiO2 and PEDOT-MWCNT/TiO2 were prepared as counter electrodes. The power conversion efficiency (PCE) increased after incorporation with carbon materials. PEDOT-NCC/TiO2 exhibits the highest PCE with the lowest charge transfer resistance.